A Facet‐Dependent Schottky‐Junction Electron Shuttle in a BiVO4010–Au–Cu2O Z‐Scheme Photocatalyst for Efficient Charge Separation. (12th June 2018) - Zhou, Chenguang; Wang, Shaomang; Zhao, Zongyan; Shi, Zhan; Yan, Shicheng; Zou, Zhigang
Abstract: Interfacial charge separation and transfer are the main challenges of efficient semiconductor‐based Z‐scheme photocatalytic systems. Here, it is discovered that a Schottky junction at the interface between the BiVO4 010 facet and Au is an efficient electron‐transfer route useful for constructing a high‐performance BiVO4 010–Au–Cu2 O Z‐scheme photocatalyst. Spectroscopic and computational studies reveal that hot electrons in BiVO4 010 more easily cross the Schottky barrier to expedite the migration from BiVO4 010 to Au and are subsequently captured by the excited holes in Cu2 O. This crystal‐facet‐dependent electron shuttle allows the long‐lived holes and electrons to stay in the valence band of BiVO4 and conduction band of Cu2 O, respectively, contributing to improved light‐driven CO2 reduction. This unique semiconductor crystal‐facet sandwich structure will provide an innovative strategy for rational design of advanced Z‐scheme photocatalysts. Abstract : Charge separation: a Schottky junction at interface between BiVO4 010 facet and Au is an efficient crystal‐facet‐dependent electron shuttle for Z‐scheme BiVO4 010–Au–Cu2 O photocatalysts and induces long‐lived photogenerated carriers, thus contributing to the improved light‐driven CO2 reduction.